MXene‐Based Composites: Synthesis and Applications in Rechargeable Batteries and Supercapacitors - Yang, Jian; Bao, Weizhai; Jaumaux, Pauline; Zhang, Songtao; Wang, Chengyin; Wang, Guoxiu (Advanced materials interfaces, 2019)
The family of 2D transition metal carbides, nitrides, and carbonitrides (collectively called MXenes) is rapidly studied since the initial synthesis of Ti3C2Tx (MXene). The surface of MXenes etched by hydrofluoric acid has hydrophilic groups (F, OH, and O), which leads the surface to be negatively charged. Consequently, the negatively charged surface can facilitate the compounding of MXenes with other positively charged materials and prevent MXenes from aggregating with some negatively charged substances, thus promoting the formation of a stable dispersion. The MXene‐based composites have better electrochemical performance than both precursors due to synergistic effects. This review elaborates and discusses the development of MXene‐based composites. It is aimed to summarize the various methods of fabricating MXene‐based composites. The applications of MXene‐based composites in batteries and supercapacitors are presented along with analysis of their excellent electrochemical performances. Finally, the authors propose the approach for further enhancing the electrochemical performances of MXene‐based composite electrode materials. After the discussion of synthesis methods, structures, and properties of MXenes, different kinds of MXene‐based composites are introduced. Thereafter, the article focuses on their synthesis methods and applications in batteries and supercapacitors. Furthermore, the ways to improve the electrochemical performance of MXene‐based composites are also analyzed. Finally, some suggestions for improving the electrochemical performance of MXenes are proposed.